The Role of Digital Citizenship Activities to Preserve Nation's Culture - Aprida Nisa Ainisyifa; Chandra Tazaka; Nadia Afifa Nugraha; Zahra Dwi Yanti; Zilan Zahrani Nursyifa; Ahmad Fuadin (CV. Rayyan Dwi Bharata, 2023)
This research focuses on the role of digital citizenship activities in preserving national culture. The purpose of this study is to find out digital citizenship on cultural preservation, what factors make this Indonesian nation's culture fade and how to preserve it. This research uses a survey method (survey research) with a descriptive design. This data collection method is done by distributing questionnaires. Participants in this study were students of the Indonesian University of Education and the general public. The results of this study indicate that the role of social media networks is very important to preserve the nation's culture.